The Effect Of Nifedipine On Oral Glucose Induced Glycaemic Changes In Normal Albino Rats - SURESHA RN; SUSHMA VN; ASHWINI V; KALABHARATHI HL; JAYANTHI MK; PRATHIMA C (International Journal of Pharma and Bio Sciences, 2012)
Aims: To determine effect of nifedipine on blood glucose levels through oral glucose tolerance test in normoglycemic albino Rats and magnitude of its effect on basal v/s glucose induced glycemic value. Methods: Normal adult albino rats of either sex weighing between 150 – 200g were randomly divided into 2 groups(n=6); Control(distilled water-1ml/rat) and Test(nifedipine-1.5mg/kg BW) and the respective drug given orally for 3 days. They were fasted overnight but with water before the 3rd day. On the 3rd day, 2 hours after the last drug dose , OGTT was performed with glucose 0.6g/kg BW. Results:The average CBG of the nifedipine group was higher compared to control group at 60, 120 and 150 minutes progressively with maximum hyperglycaemia (CBG 37.98% ) at 60 minutes after glucose administration. Conclusion: Nifedipine worsens glycaemic control in normal rats at all hours of glucose challenge. Extending this observation in human beings with overt diabetes mellitus/ high risk diabetics/ prediabetics, it is suggested to limit the use of nifedipine in situations unless absolutely necessary since it induces hyperglycaemia even in normoglycaemic rats by a postulated mechanism of inhibition of both basal and glucose induced insulin secretion significantly.